Nepalese context: Should physician treat themselves and their family members? (Journal of Kathmandu Medical College, 2015)
Physicians are individuals with families and friends and it is their duty as well as moral and social obligation to look after their friends and relatives when they become sick. But what should be their role in looking after one’s own sick family members or friends? As far as it is not as a treating physician there should be no problem but if physicians are to take responsibility of treating their family members as a physician, a number of ethical issues arise. Medical advice and medical treatment of family members is a subject of debate. The current codes of ethics of in many countries advise physicians not to treat their family members except in emergency situations and for minor illnesses. What should Nepalese physicians do?Journal of Kathmandu Medical CollegeVol. 3, No. 4, Oct.-Dec., 2014Page: 174-176